Pengembangan Buku Cerita Bergambar Berbasis Keteladanan Syekh Muhammad Kholil Kelas 4 UPTD SDN Banyuajuh 6 - Putri Sembada Nani; Tyasmiarni Citrawati (Lembaga Pengembangan Kinerja Dosen, 2023)
The aims of this development research were (1) to find out the validity of picture story books based on Syekh Muhammad Kholil's example, (2) to find out the attractiveness of picture story books based on Syekh Muhammad Kholil's example, (3) to find out the effectiveness of picture story books based on Syekh Muhammad Kholil's example. This development uses a 4D model which has 4 stages namely, Define, Design, Develop, and Disseminate. The research subjects were fourth grade students of UPTD SDN Banyuajuh 6. Based on the validation results of the experts, the following percentages were obtained, language experts 95% (very valid), material experts 85% (very valid), teaching materials experts 87.5% (very valid ), and learning design experts 90% (very valid). The attractiveness of the limited trial was the student response of 95% (very interesting), the field trial was the student response of 95.75% (very interesting), and the teacher's response was 92.5% (very interesting). The effectiveness of picture story books is obtained from learning outcomes in the cognitive domain, learning outcomes in the affective domain, teacher and student activities. Learning completeness shows 100% (classical criteria ³85% of students reach KKM). Teacher activity averaged 95% (very effective), and student activity was 92.75% (very effective). Based on the results of the research, a picture story book based on the example of Sheikh Muhammad Kholil is said to be valid, interesting, and effective so that it can be used.